Polysulfone/ Carbon Nanotubes Asymmetric Nanocomposite Membranes: Effect of Nanotubes Surface Modification on Morphology and Water Permeability - Mohammad Reza Moghbeli; Siamak Khoshrou; Ismaeil Ghasemi (Iranian Journal of Chemical Engineering)
Polysulfone/carbon nanotubes (PSF/CNTs) nanocomposite membrane was prepared via phase inversion induced by immersion precipitation technique. In addition, the surface of the CNTs were functionalized by polar carboxylic and amine groups to improve the interaction between the CNTs and the polymer matrix. For this purpose, the neat CNTs were chemically treated using sulfuric acid/ nitric acid (H2SO4/HNO3) mixture and an aromatic amine agent, i.e. 1-4-diamino benzene (DABZ), to produce the functional groups on the CNTs surface. The Fourier transform infrared (FTIR) spectra indicated the presence of carboxylic- and amine-functional groups on the nanotubes surface. Asymmetric PSF composite membrane with various levels of the functionalized CNTs were prepared to investigate the effect of functional group type on the morphology and water flux rate of the resulting membranes. The results showed that the incorporation of the functionalized CNTs up to 0.5 wt% increased the pore size and surface roughness of the sheet membranes, while further addition decreased porosity and roughness. Higher water flux rate was observed for the amine-functionalized CNTs (af-CNTs) reinforced PSF membrane when compared with the membranes reinforced with the carboxyl-functionalized CNTs (cf-CNTs). The stronger compatibility between af-CNTs and the PSF matrix caused higher water permeability. The salt rejection performance of these microfiltration composite membranes was evaluated.